Occlusive gloves and skin conditions: is there a problem? Results of a cross-sectional study in a semiconductor company - Weistenhöfer, Wobbeke; Wacker, Michaela; Bernet, Franziska; Uter, Wolfgang; Drexler, Hans (British Journal of Dermatology, 2015)
Although there is poor scientific evidence that working with occlusive gloves is as damaging as wet work, prolonged glove occlusion is considered to be a risk factor for developing hand eczema similar to wet work.To assess the effects of wearing occlusive gloves during the whole working day, without exposure to any additional hazardous substances, on skin condition and skin barrier function.We investigated 323 employees of a semiconductor production company in Germany: 177 clean-room workers wearing occlusive gloves during the whole shift (exposed group) and 146 employees working in administration (control group). A standardized interview was performed, the skin condition of both hands was studied using the quantitative skin score HEROS, and transepidermal water loss (TEWL) and stratum corneum hydration were measured.There was no significant difference in skin condition between the two subgroups. Values for TEWL and corneometry were significantly higher in exposed participants (P < 0·05). However, the TEWL values were similar to control values if participants took off the occlusive gloves at least 30 min before the measurement. Hence, the effect of occlusion on skin barrier function seems to be transient.Prolonged wearing of occlusive gloves with clean hands and without exposure to additional hazardous substances does not seem to affect the skin negatively.
EVALuna2:5457

The tissue viability imaging system—Suitable method for discovering minimal skin changes in occupational screenings? Results of a cross-sectional field study - Weistenhöfer, Wobbeke; Uter, Wolfgang; Bernet, Franziska; Drexler, Hans (Skin Research and Technology, 2019)
Background: For early detection of initial skin changes in occupational screenings, only few objective assessment systems are available. Objectives: With the aim of assessing an objective measurement method for hand eczema, we trialed the application of the tissue viability imaging (TiVi) system, quantifying erythema non-invasively by polarized light spectroscopy. Materials and Methods: In a field study with 625 employees of a semiconductor production company, 411 were exposed to prolonged wearing of occlusive gloves in the clean room. TiVi system and Hand Eczema Score for Occupational Screenings (HEROS), a quantitative skin score for the hands, were used, supplemented by a standardized personal interview. Results: TiVi values of 65 up to 246 for each hand (palm or back), for each participant summed to overall 289 up to 848 (median 389), were measured. Higher TiVi values were noted for men, smokers, and with increasing age. Correlation between TiVi and HEROS was only weak. Several factors like skin pigmentation, thickness of the skin, or tattoos seem to influence TiVi results. Conclusions: The practical relevance of one-time measurements with the TiVi system in occupational screenings seems to be limited. Specifically, the TiVi system cannot replace dermatological examinations at the workplace. Notwithstanding, the application for other scientific purposes might be useful.
CRIS-Team Scopus Importer:2019-07-23
Keywords: erythema; hand eczema; HEROS; microcirculation; prevention; skin score; TiVi